2021
DOI: 10.1039/d0cp05436d
|View full text |Cite
|
Sign up to set email alerts
|

Unusual temperature dependence of the fluorescence decay in heterostructured stilbene

Abstract: The fluorescence decay kinetics of solid stilbene demonstrate elongation of the excitation lifetime with a temperature increase. This unusual dependence can be explained by fluorescence from a thermalized exciton distribution in aggregated stilbene clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…A polystyrene matrix (Scheme 1) is used as a solid solvent because it is transparent in the spectral region to the red from 280 nm and has minimal effects on both absorption and fluorescence in the case of a single, non-aggregated sample. 25 Films were prepared in a UV-isolated room using chloroform solutions (initial PS concentration for all solutions was the same, 8 mg mL −1 ) by spin-coating (1000 rpm for 40 s, with KW-4A apparatus) onto clean 15–24 mm quartz substrates. The average film thickness ranged from 120 to 160 nm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A polystyrene matrix (Scheme 1) is used as a solid solvent because it is transparent in the spectral region to the red from 280 nm and has minimal effects on both absorption and fluorescence in the case of a single, non-aggregated sample. 25 Films were prepared in a UV-isolated room using chloroform solutions (initial PS concentration for all solutions was the same, 8 mg mL −1 ) by spin-coating (1000 rpm for 40 s, with KW-4A apparatus) onto clean 15–24 mm quartz substrates. The average film thickness ranged from 120 to 160 nm.…”
Section: Methodsmentioning
confidence: 99%
“…It is demonstrated that this type of excitonic dynamics dominates over different single-molecular excitation decay pathways in the solid phase. 25 However, detailed studies of aggregate formation of Tstilbene molecules is still lacking. Here, we present comparative studies of the absorption and fluorescence spectra as well as the fluorescence kinetics of Tstilbene solutions in a polystyrene (PS) matrix as a function of the solute concentration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assumptions about the nature of the emission from PMDs at low temperatures are based on the features of the one-dimensional structure of these dyes: the dependence of the electronic properties in the ground state and excited states on this structure [21], the manifestation of collective electronic excitations [22][23][24], the dependence of electronic properties on solvation processes that change at low temperatures [25]. The parameters of J o u r n a l P r e -p r o o f 5 quantum-chemical calculations for various molecular geometries [13][14][15]26,27] provide excellent supplementary insight to such spectral studies.…”
Section: Introductionmentioning
confidence: 99%